2021
DOI: 10.1254/jpssuppl.94.0_2-p2-lb48
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of SARS-CoV-2-induced lung injury by ACE2-like carboxypeptidase B38-CAP in COVID-19 mouse model

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a receptor for cell entry of SARS-CoV-2, and recombinant soluble ACE2 protein inhibits SARS-CoV-2 infection as a decoy. ACE2 is the carboxypeptidase to degrade angiotensin II (Ang II) to angiotensin 1-7 and improves the pathologies of cardiovascular disease and acute lung injury. To address whether the carboxypeptidase enzymatic activity of ACE2 is protective against COVID-19, we investigated the effects of B38-CAP, an ACE2-like enzyme, on SARS-CoV-2-induced lung injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ACE2 downregulation can inhibit the uptake of tryptophan, which reduces the antimicrobial peptide formation by Paneth cells, culminating in gut microbiota dysbiosis and gastrointestinal disorders related to intestinal microbiota imbalance (52). Previous reports showed that SARS-CoV-2 could decrease ACE2 expression in intestinal epithelial cells (53)(54)(55). It is thus inferred that SARS-CoV-2 infection contributes to gut microbiota dysfunction by downregulating ACE2.…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 downregulation can inhibit the uptake of tryptophan, which reduces the antimicrobial peptide formation by Paneth cells, culminating in gut microbiota dysbiosis and gastrointestinal disorders related to intestinal microbiota imbalance (52). Previous reports showed that SARS-CoV-2 could decrease ACE2 expression in intestinal epithelial cells (53)(54)(55). It is thus inferred that SARS-CoV-2 infection contributes to gut microbiota dysfunction by downregulating ACE2.…”
Section: Introductionmentioning
confidence: 99%